2022-RA-1391-ESGO Perioperative non-invasive advanced hemodynamic monitoring of patients with primary ovarian cancer undergoing multivisceral debulking surgery. (20th October 2022) - Middel, Charlotte; Stetzuhn, Matthias; Sander, Nadine; Kalkbrenner, Björn; Tigges, Timo; Pielmus, Alexandru-Gabriel; Spies, Claudia; Pietzner, Klaus; Klum, Michael; Haefen, Clarissa von; Hunsicker, Oliver; Sehouli, Jalid; et al.
Abstract : Introduction/Background: Patients undergoing high-risk surgery show an increased haemodynamic instability and have an increased risk of morbidity and mortality. However, the available haemodynamic data concentrate only on the intraoperative period. The aim of this study is to characterize patients hemodynamically throughout the whole intra- and postoperative period non-invasively by thoracic electrical cardiometry (EC) for advanced cardiovascular assessment. Methodology: In a prospective, observational, monocentric study, EC measurements were obtained before surgery, during surgery, and repeatedly throughout the hospital stay in 30 patients with primary ovarian cancer undergoing multivisceral cytoreductive surgery. The inflammatory markers interleukine-6 (IL-6) and inter-cellular-adhesion-molecule-1 (ICAM-1) were analyzed perioperatively. Severe postoperative complications were classified according to the Clavien-Dindo classification and used as a binary grouping criterion (≥3 and <2 or no complications). Results: Throughout the perioperative course, patients showed a longitudinally reduced cardiac index (CI, p<0.0001), while the stroke volume index (SVI, p=0.0528) remained unchanged. Patients suffering from postoperative complications differed over the longitudinal perioperative course in the index of contractility (ICON, p=0.0435) and the systolic time ratio (p=0.0008), without showing differences in CI (p=0.3337). Also, the groups differed during the longitudinal perioperative course in IL-6 (p = 0.0343) and ICAM-1 (p=0.0398). Conclusion: Longitudinally over the perioperative time course CI showed a relevant decrease. Patients with postoperative complications differed from patients without complications in the markers of cardiac function, ICON and STR, as well as showing a lower SVI. These data show haemodynamic alterations during surgery in all patients and especially the association of alterations to complications during the postoperative course. Therefore, they are a first approach to improve noninvasive haemodynamic patient assessments and interdisciplinary perioperative care in the future.